Religiositas dalam Keputusan Menggunakan Produk Perbankan Syariah - Indra Kurniawan (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2020)
This study aims to examine the effect of religiosity on decisions to use Islamic banking products; whether there is an influence between the facilities on the decision to use Islamic banking products; whether there is an influence between knowledge on the decision to use Islamic banking products; and whether there is an influence between promotion on the decision to use Islamic banking products. Based on the results of research and discussion, it can be concluded. First, religiosity does not have a significant effect on the variables of customer decisions in using banking products. Second, the facility has a significant influence on the customer's decision variable in using Islamic banking products. Third, knowledge has a significant influence on customer decision variables in using Islamic banking products. Fourth, the promotion has a significant influence on customer decision variables in using Islamic banking products. Fifth, religiosity does not affect, while facilities, knowledge, and promotions have a joint effect on customer decisions in using sharia banking products at BNI Syariah.